1988
DOI: 10.1063/1.455127
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation of benzene in its crystalline state: A model case for the analogy between nuclear magnetic resonance spin alignment and quasielastic incoherent neutron scattering

Abstract: Dynamic properties of dioctanoyl peroxide guest molecules constrained within the urea tunnel structure: A combined incoherent quasielastic neutron scattering and solid state 2 H nuclear magnetic resonance investigation J. Chem. Phys. 109, 4078 (1998); 10.1063/1.477008 Molecular dynamics of water in oriented DPPC multilayers studied by quasielastic neutron scattering and deuteriumnuclear magnetic resonance relaxation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…The rotary dynamics of the benzene molecules in the solvent clathrate of 2 was also investigated by 2 H NMR with crystals grown from C 6 D 6 (34). In agreement with previous studies (36,37) and as expected for a volume-conserving process, benzene molecules were found to undergo in-plane whole-body rotations described by 60°jumps with rate constants exceeding 10 8 s Ϫ1 , even at 200 K.…”
Section: Rotational Dynamics In Crystalssupporting
confidence: 57%
“…The rotary dynamics of the benzene molecules in the solvent clathrate of 2 was also investigated by 2 H NMR with crystals grown from C 6 D 6 (34). In agreement with previous studies (36,37) and as expected for a volume-conserving process, benzene molecules were found to undergo in-plane whole-body rotations described by 60°jumps with rate constants exceeding 10 8 s Ϫ1 , even at 200 K.…”
Section: Rotational Dynamics In Crystalssupporting
confidence: 57%
“…In principle, detailed analysis of F ss ∞ (t p ) can provide quantitative information about the overall geometry of the anisotropic rotational motion. 39,50 Here, we do not adopt this approach since exact determination of the plateau height is difficult in our case where the width of the decay exceeds the dynamic range of the experiment. Nevertheless, further semi-quantitative insight is available from our result that F ss ∞ continuously decreases when the evolution time is extended.…”
Section: Stimulated-echo Experimentsmentioning
confidence: 99%
“…From our simulations, we obtain u 2 equal to 0.66 Å 2 for benzene at 270 K and to 0.80 Å 2 for (PyH)I at 290 K. As mentioned above QENS data for benzene and pyridinium iodide at different temperatures are available in the literature. 16,30 For benzene at 210 K, 246 K (Fig. 6), and 273 K and for (PyH)I at 296 K and 270 K (high temperature phase) the authors found that the QENS spectra are best fitted by a sixfold rotational model between equivalent sites on a circle of radius r in the molecular plane.…”
Section: Benzene and Pyridinium Iodidementioning
confidence: 97%
“…The same geometry of motion has been proposed earlier on the basis of NMR 15,38,39 and QENS data. 16,30 As the QENS experiment is particularly sensitive to the geometry of motion, a stringent test of the simulations consist in comparing the experimental EISF (EISF experim = A 0 (Q)) with that extracted from the simulated trajectories (EISF simulated ). EISF simulated were calculated directly in nMoldyn 40 using the expression: 28…”
Section: Benzene and Pyridinium Iodidementioning
confidence: 99%
See 1 more Smart Citation